The use of interface spectrophotometric in quality control and examination of foodstuffs and raw materials - Kostenko, Elizaveta (My University, 2013)
The conditions of the immobilization dyes at the surface АВ-178 and КУ-28 were found. The interaction of Cu (II), Pb (II), Zn (II), Hg (II), Fe (III), Sn (IV), Zr (IV), Ti (IV) with the surface reagents was studied. The optimum conditions of the reactions, quantitative characteristics of the composition and the surface compounds stability; the effective dates of the modified sorbents have been obtained. A new solid-phase spectrophotometric procedures was developed for determination of the metal iones in the food objects. Визначені умови іммобілізації барвників на поверхні АВ-178 та КУ-28. Досліджена взаємодія Cu (II), Pb (II), Zn (II), Hg (II), Fe (III), Sn (IV), Zr (IV), Ti (IV) з отриманими твердофазними реагентами. Визначені: оптимальні умови реакцій, кількісні характеристики складу і стійкості поверхневих комплексів; показники ефективності іонообмінників з іммобілізованими барвниками. Розроблений ряд нових твердофазно-спектрофотометричних методик визначення металів у харчових об´єктах.
Keywords: immobilized dyes; definition the metal; фотометрія; визначення металів; іммобілізовані барвники; photometry; кафедра харчової хімії